Effects of Cosmos caudatus on sperm quality of mice, Mus musculus - Marysia Julius Booh; Nooraain Hashim; Nur Hilwani Ismail; Dzulsuhaimi Daud; Nurdiana Samsulrizal; Mohd Fakharul Zaman Raja Yahya (Penerbit Universiti Kebangsaan Malaysia, 2015)
This study was designed to analyse the effects of Cosmos caudatus on sperm quality of mice, Mus musculus. The daily intake of Cosmos caudatus was evaluated in determining its effects on male fertility. Four different concentrations of the crude ethanolic extracts which were 50 mg/kg, 125 mg/kg, 500 mg/kg and 1000 mg/kg, respectively were administered for 28 consecutive days. Sperm analyses includes sperm count, total sperm motility, sperm viability and sperm morphology were carried out using standard procedures outlined by WHO 2010. G3 group gives the highest mean percentage for change in body weight (9.60 gm), total sperm motility (56%) and normal sperm morphology count (62.8 sperm) as compared to the rest the group treatments. For the sperm count and sperm viability, G4 group showed the highest data; 56.5 million sperm/ml and 59.53%, respectively. The lowest data of the change in body weight and normal sperm morphology count of mice from G1 group which are 6.43 gm and 58.6 sperm, correspondingly. As for the sperm count, total sperm motility and sperm viability; the lowest data shown by G2 group; 39.4 million sperm/ml, 48% and 43.98%, respectively. The sperm morphology of all the treated male mice was normal except a few detected with abnormalities. The findings showed no negative effect of Cosmos caudatus on sperm quality of mice.